New Era of Muslim Women in Malay World: The Contested Women's Advancement in Decision Making Bodies - Erni Haryanti (International Journal of Nusantara Islam, 2013)
Malay world has been experiencing the conflicting and converging international influences of globalization and rapid Islamisation in many significant aspects of the countries. One of the issues is that the impact of the agenda of advancement of women‟s life to achieve gender equality promoted by international agencies. Among other women‟s improvement agenda is that woman in decision making bodies. On the other hand, the growing visible Islamic movement (and/or Islamic fundamentalism - Islamism) which may significantly grow among Malay societies would unavoidably create different ideas, attitudes and practices compared to other Muslim world. This paper explores myriad aspects of women‟s empowerment transforming into decision making bodies in the nuances of an affirmative action a recommendation of series of international conference on women. Through finding similarities and differences between the two Muslim majority countries, the support toward Muslim women‟s empowerment in decision making bodies is formally acknowledged in state regulations. Although women of Southeast Asian region are culturally recognized to have a high status and well engagement with public sphere, in the implementation of women representing themselves in political sphere has a little difference. In term of discourses Indonesia has much flourished ideas and closer to the ideas of international agenda than that of Malaysia. In the overall Malay world would gradually show its openness, tolerance and positive adaptation as a part of world society, although it cannot avoidably be departed from international agenda of both carrying Islamic and non-Islamic values.